KAJIAN TOTAL FENOL, FLAVONOID DAN AKTIVITAS ANTIOKSIDAN KACANG MERAH (Phaseolus vulgaris L.) PADA BERBAGAI LAMA WAKTU PERKECAMBAHAN - Ni Wayan Wisaniyasa; Luh Putu Trisna Darmayanti (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2019)
The purpose of this study are 1) to find out whether the length of germination times affects on the totalphenol, flavonoids and antioxidant activity of kidney bean sprouts 2). To determine the total phenol,flavonoids and antioxidant activity of kidney beans at various germination times 3). Determine the bestgermination time and the nutrient composition. The germination time in this study were 0, 24, 36, 48,60 and 72 hours. This study used a completely randomized design with three replications in order toobtain 18 experimental units. Data analysis based on ANOVA, if the treatment affects the observedvarables then tested with Duncant. The results showed that the length of germination time verysignificant effect on the total phenols, flavonoids and antioxidant activity of kidney bean sprouts. Totalphenol content of 4.46-6.33%, flavonoid levels of 1.17-9.23 mg/100 g QE, and antioxidant activity of53.91-65.10 ppm (IC 50%). The best length of germination time was 48 hours with nutritionalcomposition: water content 64.83%, ash 0.94%, fat 3.69%, protein 25.61% and carbohydrate 4.93%.